ALAT TES TAHAPAN VISUAL MOTORIK HALUS (TSUMO) UNTUK ECONOMICALLY DISADVANTAGED CHILDREN (EDC) - Sella Dermawan; Leonita Dwi Agustin; Monika Puspa Dewi; Priska Ayuningdiah Hutami; Christiany Suwartono (MANASA, 2013)
This article reports the reliability and validity of visual motor integration stages scale for economically disadvantage children (EDC). This measurement focused on visual motor integration especially in writing ability. The study consisted of 19 EDC in Sekolah Bisa! from 5-13 years old. Furthermore, this study is also adapted from the 8th stages writing ability by Gentry (2007) to Indonesian culture. The Visual Motor Integration Stages Scale (TSUMO) consists of 4 stages; basic stroke and form, words writing, phrase writing, and sentence writing. All 19 items are accepted and have correlation coeffiient >.3 using point biserial and have variation in item difficulty. It also has high reliability coefficient (r=.96) using KR20. U Mann-Whitney and internal consistency are used to determine the validity and proved to be valid. Grade norm is used to measure the norm of true score for each subject. Therefore, we can imply which stage is the subject account for from the true score of each subject. It is noted that this scale can be used to determine visual motor integration stage, especially in handwriting for EDC exclude Sekolah Bisa!